MOVIE ANALYSIS OF THE SERIES PEAKY BLINDERS - Young, Braydon; Simanjuntak, Marudud Bernadtua (Proceeding of International Conference on Islamic Education (ICIED), 2022)
The purpose of this project is to examine and analyze the moral values in the Peaky Blinders series. Includes descriptive research that produces descriptive data in the form of overall exposure in this study. Content analysis is the technique used and the origin of the data for this research is the Peaky Blinders series and previous articles. The result of this research is that this series reveals the conditions faced by poor families in the early 20th century to survive. The moral crisis is shown in this series because it adjusts to conditions that may occur at the beginning of the 20th century. This series is not recommended for children to watch because it has some scenes that are not suitable for them.